Creating the Best Possible World: Some Problems from Parfit - Cohen, Daniel (Sophia, 2009)
It is sometimes argued that if God were to exist, then the actual world would be the best possible world. However, given that the actual world is clearly not the best possible world, then God doesn’t exist. In response, some have argued that the world could always be improved with the creation of new people and that there is thus no best possible world. I argue that this reasoning gives rise to an instance of Parfit’s mere addition paradox and should thus be rejected. Others (Robert Adams, in particular) have argued that the actual world may, in fact, be the best possible world, at least for all actual people. I argue that this reasoning gives rise to Parfit’s non-identity problem and should thus be rejected.